Prevalência de anticorpos contra o vírus da influenza em equídeos de Poconé, MT - Silva, Lucas Gaíva e (2013)
The present study evaluated the prevalence of antibodies against Equine Influenza virus (EIV) in Poconé municipality, Mato Grosso state, from 529 equids by means the hemagglutination inhibition tests using H3N8 (SP/1/85) subtype as antigen. To determine the prevalence of antibodies in Poconé, each animal was pondered according to equid population in the region. Variables associated with seropositivity were evaluated by Qui-square test. Distribution and possible association among positive farms was evaluated by Spatial AutoRegressive and Multiple Linear Regression models. Of the 529 evaluated equids, 282 (53.3%) were seropositive and titers ranging from 20 to 1,280 UIH. The adjusted prevalence of EIV in Poconé municipality was estimated in 45.2% (95% IC 30.2 – 61.1%). From the evaluated farms 23 (92.0%) presented seropositive equids. Equines (54.3%), unflooded farms (66.5%), absence of vaccines program (57.8%), equine infectious anemia negativity (61.7%) and equid density above 0.086 equid/hc (62.9%) were associated to antibodies against EIV (P<0.05). No spatial correlation was found (P>0.05) among studied farms, however those farms located in unflooded areas were associated with EIV antibodies (P<0.05). Negative correlation was observed between the prevalence of EIV antibodies and presence of EIAV positive animals on farms. The high prevalence of EIV antibodies found in the present study suggest viral activities among equids and statistical analyses indicate that animal transit and agglomeration were associated factors to the virus transmission in the region.